Three-dimensional volume-rendered computed tomography application for follow-up fracture healing and volume measurements pre–surgical rib fixation and post–surgical rib fixation. Issue 6 (December 2021) - Campbell, Don; Arnold, Nicholas; Wake, Elizabeth; Grieve, John; Provenzano, Sylvio; Wullschleger, Martin; Patel, Bhavik
Abstract : BACKGROUND: Surgical rib fixation (SRF) is being used increasingly in trauma centers for stabilization of chest wall injuries, in line with new and evolving surgical techniques. Our institution has developed a pathway for the management of chest wall injuries and SRF, which includes a follow-up low-volume, noncontrast computed tomography (CT) scan at 12 months. METHODS: This study was a single-center retrospective study conducted on 25 consecutive patients who underwent SRF between February 2019 and February 2020. All CT measurements were done by a CT radiographer under the supervision of a board-certified radiologist and included the use of three-dimensional volume-rendered images. RESULTS: There were no patients with SRF who experienced hardware failure at 12 months in either flail or nonflail groups. For fractured ribs treated with SRF, complete or partial union occurred in 75 of 76 ribs plated (98.7%). The median ratio for improvement in lung volumes was 1.71 for flail SRF and 1.69 for nonflail SRF in our study. CONCLUSION: Three-dimensional volume-rendered CT at 12 months post-SRF showed good alignment (no hardware failure) and fracture healing of fixed ribs in both flail and nonflail groups. Lung volumes also improved pre-SRF and post-SRF for both flail and nonflail patients. More studies are needed to define how the pattern of rib fracture healing of fixed and nonfixed ribs affects lung volumes. LEVEL OF EVIDENCE: Therapeutic, Level V.